Design of Artificial-Material-Based Antennas Using Inverse Scattering Techniques - Palmeri, Roberta; Bevacqua, Martina Teresa; Morabito, Andrea Francesco; Isernia, Tommaso (IEEE transactions on antennas and propagation, 2018)
A new approach to the design of graded artificial materials (GAMs)-based devices is proposed by exploiting the inverse scattering framework as a synthesis tool. The introduced general methodology can be applied to arbitrary far-field specifications, thus allowing the design of noncanonical devices. In particular, two different strategies are developed for GAMs based on either graded refractive index (GAM _{R} ) or graded filling factor (GAM _{F} ). In both strategies, the inverse scattering problem is solved by a proper reformulation of the contrast source inversion method, wherein a proper rescaling of the amplitude of the primary sources is also used. In particular, in the first strategy, the GAM _{F} is obtained by exploiting homogenization theories. In the second strategy, the GAM _{R} is synthesized by exploiting a suitable representation basis for the unknown contrast function, and then simple analytical formulas are used to determine the corresponding GAM _{F} . The proposed approach is assessed through the synthesis of an antenna generating a \Sigma /\Delta reconfigurable pattern.